Experimental Research On The Development Of Extemporaneous Ointment ForThe Treatment Of Proctologic Diseases - Pul-Luzan V.V. (Journal of Global Pharma Technology, 2020)
Hemorrhoids are the most common proctological diseases affecting an average of 12 people out of 100. Hemorrhoid affects more than 10 % of the adult population of the planet, and the proportion of the total number of proctological diseases is 40 %. Hemorrhoid is the most common reason to see a proctologist. Therefore, the problem of choosing the tactics of treatment of this category of patients remains relevant. If constipation is called “intellectual disease”, then hemorrhoid is called “royal disease”. Men and women suffer from this disease equally. In women, exacerbation of hemorrhoid often occurs during pregnancy, usually in the last trimester. Sooner or later, enlargement of the hemorrhoid appears in most people.The objective of this work is the development of extemporaneous ointment for the treatment of proctologic diseases. To achieve this goal the following tasks were solved: the literature on the current state of such diseases as hemorrhoids has been analyzed and summarized; the range of medicines used to treat hemorrhoids has been analyzed. As a result the composition of the combined ointment for the treatment of hemorrhoid has been substantiated and its technology has been developed, the stability and microbiological purity of the created extemporaneous combined ointment has been studied.